Função discursiva em sujeitos nominais marcados supra-segmentalmente (Revista de Estudos da Linguagem, 1993)
This paper demonstratel! emplrical evldences for a functional hypothesls about the language prosodic leveI. Modem Brazilian Portuguese data shaw that the noun phrases, wh1ch have a certaln supra-segmental feature, are llnlts ln discourse. Pragmatic motivations are aIso discussed, spec1a1ly the lnteractional polnt of view.